2011
DOI: 10.3171/2010.9.spine09828
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of prevertebral soft-tissue swelling and dysphagia in multilevel anterior cervical discectomy and fusion with recombinant human bone morphogenetic protein–2 in patients at risk for pseudarthrosis

Abstract: Object The goal of this study was to demonstrate the incidence of fusion and soft-tissue swelling in multilevel anterior cervical discectomies and fusions (ACDFs) using polyetheretherketone (PEEK) spacers with recombinant human bone morphogenetic protein–2 (rhBMP-2) impregnated in a Type I collagen sponge and titanium plates. Methods A single surgeon performed 30 multilevel ACDFs using PEEK spacers with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
51
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 19 publications
0
51
0
1
Order By: Relevance
“…The authors also reported that while most patients complained of neck swelling there were no cases of reintubation due to airway compromise and no patients returned to the operating room for postoperative hematoma or seroma evacuation. Similarly, Stachniak et al reported a 95 % fusion rate at 6-months and a 100 % fusion rate at 9-months following a 2-or 3-level ACDF with rhBMP-2 in a group with substantial risk factors for pseudarthrosis (33 % smoking, 13 % diabetes, and 43 % obesity) [53]. In another retrospective cohort study comparing multilevel ACF with and without rhBMP-2, the authors demonstrated a 100 % fusion rate in the rhBMP-2 cohort vs an 82.6 % fusion rate in the group without rhBMP-2 [44].…”
Section: Arguments In Favor Of Bmp Utilization In the Anterior Cervicmentioning
confidence: 90%
See 1 more Smart Citation
“…The authors also reported that while most patients complained of neck swelling there were no cases of reintubation due to airway compromise and no patients returned to the operating room for postoperative hematoma or seroma evacuation. Similarly, Stachniak et al reported a 95 % fusion rate at 6-months and a 100 % fusion rate at 9-months following a 2-or 3-level ACDF with rhBMP-2 in a group with substantial risk factors for pseudarthrosis (33 % smoking, 13 % diabetes, and 43 % obesity) [53]. In another retrospective cohort study comparing multilevel ACF with and without rhBMP-2, the authors demonstrated a 100 % fusion rate in the rhBMP-2 cohort vs an 82.6 % fusion rate in the group without rhBMP-2 [44].…”
Section: Arguments In Favor Of Bmp Utilization In the Anterior Cervicmentioning
confidence: 90%
“…Although multiple complications associated with BMP utilization in cervical fusion procedures have been reported, there is evidence that the complication rates are dose related and decrease with lower doses [53]. Importantly, Frankel et al reported no complications when the dosage of rhBMP-2 was less than 1.1 mg/level [44].…”
Section: Arguments In Favor Of Bmp Utilization In the Anterior Cervicmentioning
confidence: 99%
“…Stachniak et al reported that only 6.7% of their patients had persistent dysphagia with low dose rhBMP-2, 6 months after their procedure (10). Similarly, Kukreja et al reported lower incidence of postoperative dysphagia with lower rhBMP-2 doses (11).…”
Section: Editorialmentioning
confidence: 98%
“…36 Controversy over its use, however, has also increased over the years 18,42 with several studies reporting complications. 3,8,10,30,41,[45][46][47][48]51,52,55 One of the justifications for its use has been its cost savings associated with prevention of fusion failures. 1,19,39 A few studies have advocated for its use in the posterior cervical spine because of its high fusion rates.…”
mentioning
confidence: 99%